2003
DOI: 10.1023/a:1024487804497
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced anti-predator defences in plankton: a review

Abstract: Planktonic organisms exhibit diverse morphological, behavioural and life-history responses to the chemical presence of potential predators. Prey organisms have been found to sense such predators via predator-derived kairomones. The induced reactions are assumed to reduce predation risk and thus to be adaptive. Numerous studies have investigated various aspects of inducible defences in different crustaceans, in rotifers, planktonic ciliates and algae. As a first step, we summarise recent work on chemically indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
261
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(280 citation statements)
references
References 204 publications
(307 reference statements)
4
261
1
2
Order By: Relevance
“…Experiment 3 suggests that these chemicals are large enough to be removed by a 0.46-µm filter, as Mysis water that had been filtered through such a fine filter had little or no effect on Mysis vertical position. This may offer a clue into the identity and properties of the kairomones, which are not well-known or understood in invertebrate predator-prey systems (Lass and Spaak 2003). Note that Experiment 4 suggests that the cue is not associated with alarm signals from conspecifics (Pijanowska 1997) because D. mendotae responded to water that never contained conspecifics, but rather only contained Mysis previously fed D. mendotae.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Experiment 3 suggests that these chemicals are large enough to be removed by a 0.46-µm filter, as Mysis water that had been filtered through such a fine filter had little or no effect on Mysis vertical position. This may offer a clue into the identity and properties of the kairomones, which are not well-known or understood in invertebrate predator-prey systems (Lass and Spaak 2003). Note that Experiment 4 suggests that the cue is not associated with alarm signals from conspecifics (Pijanowska 1997) because D. mendotae responded to water that never contained conspecifics, but rather only contained Mysis previously fed D. mendotae.…”
Section: Discussionmentioning
confidence: 96%
“…Predator-induced changes in vertical position and diel migration timing of Daphnia and other zooplankton in both freshwater and marine systems have been well documented (Frost and Bollens 1992, Fortier et al 2001, Irigoien et al 2004, reviewed in Hayes 2003, and Lass and Spaak 2003. Typically, movement is in a direction that is adaptive and reduces predation risk.…”
Section: Discussionmentioning
confidence: 99%
“…Forward and Rittschof (2000) showed that in the reaction of crab larvae (Rhithropanopeus harrisii) to the presence of fish polysaccharides played a role, whereas the spiny lobster Panulirus argus used mixtures of different substances to discriminate between different predators (Fine-Levy et al 1989). In many other well-known examples of chemical communication the chemical structure of the substances involved remains unclear (Lass and Spaak 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the last decade, it has become increasingly clear that chemicals excreted by predators (kairomones) can influence a wide range of characteristics in their prey species. In aquatic environments, predator kairomones have been shown to affect morphology, life-history traits and behaviour of prey species (reviewed by Harvell, 1990;Larsson & Dodson, 1993;Lass & Spaak, 2003). These predator-prey communication links have been found throughout aquatic foodwebs.…”
Section: Introductionmentioning
confidence: 99%